2009
DOI: 10.1073/pnas.0912924107
|View full text |Cite
|
Sign up to set email alerts
|

Optimal hematocrit for maximal exercise performance in acute and chronic erythropoietin-treated mice

Abstract: Erythropoietin (Epo) treatment increases hematocrit (Htc) and, consequently, arterial O 2 content. This in turn improves exercise performance. However, because elevated blood viscosity associated with increasing Htc levels may limit cardiac performance, it was suggested that the highest attainable Htc may not necessarily be associated with the highest attainable exercise capacity. To test the proposed hypothesis that an optimal Htc in acute and chronic Epotreated mice exists-i.e., the Htc that facilitates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 33 publications
4
102
2
Order By: Relevance
“…Therefore, the pattern of the relationship between haematocrit and Ṁ sum seemed to parallel that observed between pectoral muscle size and Ṁ sum . The parabolic shape in the relationship between Ṁ sum and haematocrit is consistent with the idea that beyond a certain level, the benefit of increasing oxygen carrying capacity is counterbalanced by the disadvantage of elevated blood viscosity (Schuler et al, 2010;Williams et al, 2012). Therefore, it could be that chickadees have an optimal haematocrit level that maximizes their heat production capacity and cold endurance, and given that heart mass fluctuates seasonally in small wintering passerines (e.g.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Therefore, the pattern of the relationship between haematocrit and Ṁ sum seemed to parallel that observed between pectoral muscle size and Ṁ sum . The parabolic shape in the relationship between Ṁ sum and haematocrit is consistent with the idea that beyond a certain level, the benefit of increasing oxygen carrying capacity is counterbalanced by the disadvantage of elevated blood viscosity (Schuler et al, 2010;Williams et al, 2012). Therefore, it could be that chickadees have an optimal haematocrit level that maximizes their heat production capacity and cold endurance, and given that heart mass fluctuates seasonally in small wintering passerines (e.g.…”
Section: Discussionsupporting
confidence: 59%
“…Winter increases in haematocrit are therefore interpreted as a physiological upregulation in response to elevated oxygen demands for thermogenesis (Carey and Morton, 1976;Swanson, 1990b), which likely maximizes heat production capacity and cold endurance. However, increasing the number of cells in circulation also increases blood viscosity, which suggests that the relationship between haematocrit and thermogenic capacity should not be linear but rather dome shaped, with an optimal haematocrit found at intermediate levels (Schuler et al, 2010), which may vary among seasons depending on heart size adjustments (e.g. Liknes and Swanson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Under normoxia, a moderately increased Hct augments arterial O 2 content and therefore enhances aerobic capacity (Ekblom and Hermansen, 1968;Kanstrup and Ekblom, 1984;Ekblom and Berglund, 1991). However, the highest attainable Hct is not necessarily associated with the highest attainable aerobic power output (Crowell et al, 1959;Crowell and Smith, 1967;Villafuerte et al, 2004;Schuler et al, 2010). This is because the associated increase in blood viscosity produces a higher peripheral vascular resistance that might compromise Q, thereby reducing V O2,max (Guyton and Richardson, 1961;Connes et al, 2006).…”
Section: Erythropoeitic Activitymentioning
confidence: 98%
“…However, results of several empirical and theoretical studies suggest that increasing the Hb concentration of partially saturated blood is not an ideal long-term solution to the problem of chronic hypoxemia because the associated increase in blood viscosity produces an elevated peripheral vascular resistance that can compromise cardiac output (Guyton and Richardson, 1961;Bullard, 1972;McGrath and Weil, 1978;Winslow and Monge, 1987;Monge and León-Velarde, 1991;Connes et al, 2006;Schuler et al, 2010;Storz, 2010). Studies of humans at high altitude have suggested that the optimal Hb concentration at rest and at exercise may actually be quite close to the typical sea level value (Winslow, 1988;Villafuerte et al, 2004), or perhaps only slightly higher (Reeves and León-Velarde, 2004), and it is well documented that excessive polycythemia is a causal factor in the development of chronic mountain sickness (Winslow et al, 1985;Winslow and Monge, 1987;Monge and León-Velarde, 1991;Rivera-Ch et al, 2007).…”
Section: Introductionmentioning
confidence: 99%